Sedimentation Profile in Coastal Water Jakarta Bay: Profil Sedimentasi Perairan Pesisir Teluk Jakarta - Yonvitner; Nandi Abdul Aziz; Sigid Hariyadi; Syamsul Bahri Agus; I Wayan Nurjaya (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2022)
The waters of Jakarta Bay are one of the waters that are influenced by several fresh water flows that enter from the DKI Jakarta area and its surroundings. Sediment that enters the waters of Jakarta Bay is produced by the activities of the people who live in the Jakarta area and its surroundings. This study aims to analyze the sedimentation and distribution of suspended solids in the Jakarta Bay estuary using an observational approach and spatial analysis. This study uses the Inverse Distance Weighting (IDW) interpolation method. The dominant distribution of sediment in Jakarta Bay is sand with a size ranging from 0.25 to 0.125 mm. TSS (Total Suspended Solids) levels in 11 estuaries in Jakarta Bay ranged from 21 to 150 mg/L in first period and 11 ˗ 259 mg/L in second period. Sedimentation rates that occurred in 11 Jakarta Bay estuaries ranged from 11.12 g/cm2/day to 619.5 g/cm2/day in period one and 10.96 g/cm2/day to 1232.06 g/cm2/day in the second period which is located in Muara Cilincing in both periods. There is a suitable relationship between the TSS value and the sedimentation rate. Estuary TSS values and sedimentation rates are influenced by seasons and anthropogenic activities that occur in the estuary such as reclamation.